Stability parameters in bottle gourd (Indian Journal of Arid Horticulture, 2025)
In this investigation an elite genotype of spineless cactus pear was selected for in vitro propagation. The effect of different levels of BA (0, 3.0, 6.0 and 9.0 mg 1') and NAA (0, 0.1 and 1.0 mg 1') alone and in combination were evaluated for in vitro culture establishment, axillary bud breaking, micro-shoot formation and root initiation. Early axillary bud breaking in cladode explant was induced with 9.0 mg BA +0.1 mg NAA I' in 19.47 days, whereas all NAA concentrations failed to induce bud breaking in the explants. However, root initiation was noticed with NAA concentrations of 0.1 and 1.0 mg I". Culture establishment in terms of percentage of explant with microshoot was maximum (80%) with 6.0 mg BA1+0.1 mg NAA I' as compared to minimum (26.67%) with 3.0 mg BA 1 and 1.0 mg NAA 1' treatment. All treatments of BA alone and in combination with NAA found to induce micro-shoots in single bud/areole of cladode explant. The proliferated micro-shoots were subjected for elongation treatment in order to obtain rootable length of micro-shoots. The elongated micro-shoots were further subjected to root formation under in vitro condition with different concentrations of NAA (0, 2.0, 4.0 and 6.0 mg 1'') and IBA (2.0, 4.0 and 6.0 mg 1'). Maximum number of roots was recorded with 6.0 mg IBA I. Further the length of roots was also maximum (3.80 cm) with 6.0 mg IBA I. The rooted plantlets were successfully acclimatized and approximately 92 per cent success obtained in potting mixture of vermiculite and cocopeat 3: 1 (v/v)
Keywords: Cactus pear; micropropagation; acclimatization